2005
DOI: 10.1002/dc.20220
|View full text |Cite
|
Sign up to set email alerts
|

Chest wall abscess: An unusual presentation of Hodgkin's lymphoma

Abstract: A chest wall abscess is a very rare presentation of extranodal Hodgkin's lymphoma (HL); only one case has been reported to date. Here, we describe a case of a 38-yr-old man with HL whose initial presentation was a chest wall abscess. The diagnosis of HL was suggested by cytological examination of the purulent discharge and was confirmed subsequently by excisional biopsy of cervical lymph node.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There have been previous reports of abscess presentations for Hodgkin’s disease and include in the liver,26 lung,27 brain28 and chest wall 29. We found only one report in the literature for suppurative lymphadenitis as the primary presenting feature for Hodgkin’s disease 30…”
Section: Discussionmentioning
confidence: 70%
“…There have been previous reports of abscess presentations for Hodgkin’s disease and include in the liver,26 lung,27 brain28 and chest wall 29. We found only one report in the literature for suppurative lymphadenitis as the primary presenting feature for Hodgkin’s disease 30…”
Section: Discussionmentioning
confidence: 70%
“…Review of literature corresponding to our 15‐year study period (2000‐2015) revealed 20 reports based either on cases series or isolated cases (Table ) in which 26 histologically confirmed chest wall lymphoma cases were described . Location of the swellings was the anterior chest wall/manubrium in 14 cases, left chest wall (four cases), right chest wall (three cases), lateral chest wall (NOS in two cases), back in one case and rib/chest wall swellings and NOS in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other lymphoma subtypes such as Hodgkin's lymphoma, large anaplastic cell, panniculitis‐like T‐cell lymphoma and Burkitt lymphoma have been reported much less frequently among chest wall swellings. The frequency of lymphomas other than DLBCL from the literature review were as follows: Hodgkin's lymphoma (six cases), Burkitt lymphoma (two cases), ALCL (two cases), and marginal zone B‐cell lymphoma, B‐cell lymphoma (NOS), subcutaneous panniculitis‐like T‐cell lymphoma (SCPTCL), diffuse medium‐size B‐cell lymphoma and null cell NHL in one case each.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations